Advancing public health competencies: a practice-driven pedagogical reform integrating case studies, fieldwork, and digital simulation - Zheng, Zhanyue; Kang, Cheng; Wang, Chengqiang; Li, You; Sun, Yan (Frontiers in Education, 2025)
IntroductionTraditional teaching methods in public health graduate education are often limited by low student engagement and insufficient practical skill development. To address these challenges, a reformed pedagogical model was introduced for the “Occupational Environment and Population Health” module in the Guilin Medical University Master of Public Health program (2023 cohort).MethodsThe reform integrated case-based learning, field immersion, and digital simulation technologies within smart classroom ecosystems. A total of 35 students in the reform cohort were compared with a traditional cohort. Knowledge acquisition was assessed through longitudinal testing (pretest, posttest, delayed posttest). Questionnaire-based evaluation measured problem-solving ability, professional knowledge mastery, learning motivation, and career orientation. Factor analysis was conducted to validate the evaluation framework.ResultsThe reform cohort achieved significantly higher knowledge scores (82.09 ± 1.88) compared with the traditional cohort (79.71 ± 1.70, p < 0.05). Longitudinal assessments indicated superior knowledge retention in the reform group. Questionnaire results confirmed notable improvements in problem-solving ability, professional knowledge, learning motivation, and career orientation. Factor analysis validated a three-dimensional evaluation framework encompassing Career Development, Competency Enhancement, and Course Satisfaction, confirming its reliability.DiscussionThis study provides preliminary empirical evidence supporting the effectiveness of case-based, practice-oriented pedagogy in enhancing learning outcomes in public health education. While findings highlight improved knowledge, satisfaction, and career readiness, broader validation across larger and more diverse student populations is required to confirm the generalizability of this approach.